Darke - Sage, Angie (Sage, Angie. Septimus Heap, 2011)
Alther Mella has been Banished, a Darke Domaine engulfs the Castle, and a Darke dragon is on the loose. Septimus Heap must use all of his skills to save the Castle and the Wizard Tower from destruction.